Optical and Electrical Properties of SnO2:F Thin Films Obtained by R.F. Sputtering With Various Targets. (1991) - Geoffroy, C.; Campet, G.; Menil, F.; Portier, J.; Salardenne, J.; Couturier, G.
Abstract : Tin oxide films were deposited on glass substrates by reactive and non reactive r.f. sputtering using different types of targets corresponding to various Sn/F atomic ratio: hot pressed Sn–SnF2 or SnO2 –SnF2 mixtures, ceramics obtained by casting either an aqueous SnO2 –SnF2 slurry or a suspension of tin oxide in molten tin fluoride. The samples were prepared in oxygen-argon gas mixtures in which the oxygen concentration was varied from 0 mole % up to 30 mole% depending on the target. The optical and electrical properties of the obtained thin films have been studied and compared to those of the films obtained by spray technique.